Knowing from the indigenous North
1 online resource
Keywords: "Focusing on the Sápmi region of Northern Europe as a point of departure, this book enriches and sharpens the concept of 'the North.' It combines detailed empirical research on the Sámi people and their life-worlds with theoretical contributions from leading scholars. The authors consider the European North not only as a geographical site or an object of academic research, but as a particular way of knowing and being, with its own needs, practices, concepts, and imaginings. The North, as an epistemic position, offers its own conceptions of politics, human agency, history, and social relations, which this book studies and describes. The volume challenges us to consider social scientific knowledge, its significance, and the practices of producing it in a new way."--